Implementation of Coffee Production Strategy at the Jember Kahyangan Plantation Regional Public Company - Siswanto, Adil; Nurizzahroh, Iftah Tazkiyatu; Rohma, Laila Saniatur; Abror , Nasichul (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This research explores coffee production strategies at Jember Kahyangan Plantation Regional Public Company, focusing on optimizing productivity, efficiency, and sustainability. Method: A qualitative approach was used through observation, interviews, and documentation. The findings show that Perumda Perkebunan Kahyangan Jember produces robusta coffee with meticulous processing to ensure quality. Practical Application: Coffee is one of the agricultural commodities that is quite tempting to develop, seeing the market potential reaching overseas so that in its development, coffee is experiencing modernization. Coffee production in Indonesia always increases every year. Indonesia is the world's fourth exporter of coffee commodities with an average role of 4.76 percent of total world exports. The Jember Kahyangan Plantation Regional Public Company is one of the companies engaged in processing coffee production. Conclusion: A production strategy is a detailed plan designed to organize and manage a company's production processes to achieve predetermined goals, including efficiency, product quality and customer satisfaction. The definition above shows that a company needs a strategy so that the company does not go bankrupt.